Alopecia in Bats from Tropical Urban Islands - Fauziah Syamsi; Wilson Novarino; Dahelmi Dahelmi; Chairul Chairul (JURNAL PEMBELAJARAN DAN BIOLOGI NUKLEUS, 2025)
Background: Alopecia or alopecic syndrome is a hair loss condition on the body. Alopecia is caused by a wide variety of factors both internal to the individual (i.e. androgen activity, nutritional deficiencies, metabolic stress, hormonal imbalances) and external (i.e. human-induced pressures, allergens, ectoparasites, fungal dermatitis, bacterial, toxicities, environmental contaminant exposure, idiopathic disease, poor habitat conditions, anthropogenic activities, zinc deficiency, and ingestion of plant toxins). Methods: This study was conducted at four locations in Batam City, consisting of two fragmented forests in the city center and two islands far from the city area. Bats were captured using mist nets and harp traps with a total sampling effort of 120 net nights and 120 harp trap nights. Findings: This study captured 417 bats across seven species, with an overall alopecia prevalence of 10.79 %. The highest prevalence was found in Pipistrellus tenuis (100%), Kerivoula pellucida (50 %), and Macroglossus minimus (20 %), likely due to the small sample sizes of these species. Larger sample sizes resulted in lower prevalence rates: Balionycteris maculata (22.2 %), Cynopterus horsfieldii (11.1 %), C. brachyotis (9.2 %), and C. sphinx (6.86 %). The most severe hair loss generally occurs on the shoulders and neck. Some individuals show hair loss on the back, head, chest, abdomen, and other parts of the body. Alopecia is found in both males and females from mild to severe. The prevalence of alopecia in all species was higher in fragmented forests in urban to periurban, and rural areas. This was associated with differences in the level of anthropogenic pressure. Contribution: These findings provide a scientific contribution to understanding the relationship between alopecia in bats and anthropogenic pressures and highlight the importance of habitat conditions in population health in fragmented environments.